PENGARUH POLA ASUH ORANG TUA DAN LINGKUNGAN SEKOLAH TERHADAP AKHLAK SISWA SMP SEDERAJAT - Didit Darmawan; Achmad Irsyadul’Ibad; Adam Arrisallah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study was motivated by the importance of the role of family and school as the two main environments in shaping the character and behavior of students. The purpose of this literature review study is to examine how parenting patterns and the educational environment influence the character of junior high school students. The research method used is a literature study by examining various research results from relevant accredited national journals. This is a qualitative study. The results indicate that parenting styles and the school environment play a positive and significant role in shaping students' morals, both when the two interact simultaneously and when each stands alone. Democratic parenting proved to be the most effective in fostering commendable character, such as responsibility, politeness, and honesty, while a conducive, disciplined, and religious school environment also strengthened the process of internalizing moral values in students' daily lives. Furthermore, the synergy between families and schools contributes significantly to shaping consistent and sustainable moral character. Thus, the results of this research synthesis confirm that the formation of students' moral character is not only the responsibility of schools, but also the result of harmonious interaction between family parenting styles and the school environment.